A Descriptive Study on the Prevalence and Risk Factors of two Killing Diseases: Hepatitis B (HBV), Hepatitis C (HCV) - Namrah Asif, Nimra Arif, Syeda Maria Habib, Zarmina Taimur, Amir Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis B (HBV), and Hepatitis C (HCV) are the two most frequent diseases all over the world, and also the main cause of mortality around the world. In Pakistan HBV and HCV, the Patient population is too high, especially in rural areas. Objective: This study aimed to examine the risk factors that cause HBV and HCV and their prevalence, also sex and gender evaluation. Material and Methods: This descriptive study was conducted in Services Hospital Lahore, from February 2021 to January 2022. In this study, we included 1050 patients with chronic liver failure to examine the frequency and risk factors of Hepatitis B and Hepatitis C viruses. Results: In this study, we examined 1050 patients with liver diseases, out of 1050 We found 135 patients had both Hepatitis B (HBV) and Hepatitis C (HCV), 55 (5.23%) patients were found +Hepatitis C, and 80 (7.62%) patients were found +HBV. The mean age calculated was 36.05 years. Of 135 patients of HBV and HCV, men were 45 (33.33%) and 68 (50.37%) were women while 22 patients were aged <18 years. We observed most frequently Hepatitis B and C in the patients between the ages of 20 to 35 years (45 (56.25%) patients of +HCV and 33(60%) patients of HBV viruses respectively). We found the most prevalent in women (HBV infection women 44(55%) and 24(50.9%) women had HCV). In this study, we also included the detailed history of patients such as age, sex, socio-economic status, literacy, poverty, use of pipe-lined water or pumped water, smoking history, use of drugs with used injection, blood donation history, and organ transplantation history. Practical implication: Women and adults needs vaccination for HBV and HCV because they affected more. Conclusion: In this study, we found the frequency of these two killing infections HBV and HCV is too high compared to the other developed countries. Mostly women and adults were affected by these viruses. Keywords: Hepatitis B, Frequency, Virus, Diseases, Infections.